Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41467-020-15197-w
|View full text |Cite
|
Sign up to set email alerts
|

δ and φ back-donation in AnIV metallacycles

Abstract: In all known examples of metal-ligand (M-L) δ and φ bonds, the metal orbitals are aligned to the ligand orbitals in a "head-to-head" or "side-to-head" fashion. Here, we report two fundamentally new types of M-L δ and φ interactions; "head-to-side" δ and "side-to-side" φ back-bonding, found in complexes of metallacyclopropenes and metallacyclocumulenes of actinides (Pa-Pu) that makes them distinct from their corresponding Group 4 analogues. In addition to the known Th and U complexes, our calculations include c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 78 publications
7
38
0
1
Order By: Relevance
“…In opposition to this, when the donor was Te instead, the M–Te lengths increased gradually to reach a maximum at Am before a sharp drop at Cm. One way of interpreting this is to consider that the U–Te bond has a much larger covalent contribution than that of an Am‐Te bond and is thus much shorter than it would be if purely ionic [28] . Simultaneously, calculations predict larger deviation from formal f orbital population at the Am 3+ center than that of U 3+ in model 6‐coordinate [M{N(Se=PH 2 ) 2 } 3 ] and that a similar observation is seen for Eu 3+ in the Ln series [13c] .…”
Section: Resultsmentioning
confidence: 99%
“…In opposition to this, when the donor was Te instead, the M–Te lengths increased gradually to reach a maximum at Am before a sharp drop at Cm. One way of interpreting this is to consider that the U–Te bond has a much larger covalent contribution than that of an Am‐Te bond and is thus much shorter than it would be if purely ionic [28] . Simultaneously, calculations predict larger deviation from formal f orbital population at the Am 3+ center than that of U 3+ in model 6‐coordinate [M{N(Se=PH 2 ) 2 } 3 ] and that a similar observation is seen for Eu 3+ in the Ln series [13c] .…”
Section: Resultsmentioning
confidence: 99%
“…The d bonding interaction in these inverse sandwich samarium biphenyl complexes is reminiscent of recently identied inverse sandwich lanthanide-boron binary clusters 73,74 and actinide metallacycles. 75…”
Section: àmentioning
confidence: 99%
“…It was previously found that AdNDP is basis-set and method independent. [53][54][55] It revealed three stype lone pairs on Al atoms with occupation numbers (ONs) of 1.96-1.67 |e|, two s-type lone pairs on two B atoms with ON=1.46 |e|, one 2c-2e B-B σ bond with ON=1.89 |e|, and two 5c-2e π bonds involving all B and Al atoms with ON=2.00|e|. The last two fully delocalized 5c-2e bonds could also be viewed as two direct B-B 2c-2e π bonds with somewhat lower ON values, i.e.…”
mentioning
confidence: 99%